2023
DOI: 10.1002/cam4.5585
|View full text |Cite
|
Sign up to set email alerts
|

ITGB3 promotes cisplatin resistance in osteosarcoma tumors

Abstract: Objective Osteosarcoma is the most malignant and common primary bone tumor with a high rate of recurrence that mainly occurs in children and young adults. Therefore, it is vital to facilitate the development of novel effective therapeutic means and improve the overall prognosis of osteosarcoma patients via a deeper understanding of the mechanisms of chemoresistance in osteosarcoma progression. Methods In this research, the relationship between ITGB3 and the clinical characteristics of patients was detected thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…ITGB3 has been found to play a vital role in tumors. In osteosarcoma, ITGB3 performed the functions of proliferation and cisplatin resistance through the MAPK and VEGF signaling pathways [ 18 ]. ITGB3 is upregulated by sponging miR-124-3p, consequently enhancing the proliferation, migration, and invasion of the cells in gastric cancer [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…ITGB3 has been found to play a vital role in tumors. In osteosarcoma, ITGB3 performed the functions of proliferation and cisplatin resistance through the MAPK and VEGF signaling pathways [ 18 ]. ITGB3 is upregulated by sponging miR-124-3p, consequently enhancing the proliferation, migration, and invasion of the cells in gastric cancer [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the anti-cancer effects of HYSA in the MG63 cells by using an FPT inhibitor were assessed by the method of Yang et al [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…VDAC1 promotes OS cell proliferation and apoptosis through the MAPK signaling pathway 198 . Transcriptome analysis showed that ITGB3 functions in OS through the MAPK and VEGF signaling pathways for cell proliferation and cisplatin resistance 199 . Protein serine kinase H1 (PSKH1) is an autophosphorylated human protein serine kinase.…”
Section: Signaling Pathways In Osmentioning
confidence: 99%
“… 198 Transcriptome analysis showed that ITGB3 functions in OS through the MAPK and VEGF signaling pathways for cell proliferation and cisplatin resistance. 199 Protein serine kinase H1 (PSKH1) is an autophosphorylated human protein serine kinase. β‐Phenylethyl isothiocyanate induces the proliferation of human OS cells by changing iron metabolism, disrupting redox homeostasis, and activating the MAPK pathway.…”
Section: Signaling Pathways In Osmentioning
confidence: 99%